Strategi Komunikasi Humas Siantar Zoo dalam Promosi Destinasi Wisata Edukasi - Shaqiula Devina Amanda; Indira Fatra Deni (Avant Garde, 2026)
The development of digital media has transformed tourism promotion practices, including educational tourism, which requires effective communication strategies to reach the public. As an educational tourism destination, Siantar Zoo utilizes digital media to disseminate information, build its image, and increase public engagement. This study aims to analyze the public relations communication strategy of Siantar Zoo in promoting educational tourism through digital media. The study employed a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and documentation with Mr. Bagaskara, the Public Relations and Information Officer of Siantar Zoo, as the main informant. The findings reveal that Siantar Zoo utilizes Instagram, TikTok, and Facebook as the primary platforms for promotion and information dissemination. The communication strategy is implemented through educational content related to wildlife, conservation, tourism activities, and learning programs, presented in the form of photographs, reels, and short videos adapted to current social media trends. The study also found that active interaction through comments, direct messages, and reposting visitors’ content contributes to effective two-way communication and strengthens relationships with the public. Furthermore, transparent information regarding animal care and educational activities helps enhance public trust in Siantar Zoo. The findings indicate that the integration of digital media utilization, educational content development, and sustainable public engagement plays a significant role in strengthening Siantar Zoo’s positive image as an educational tourism destination and increasing public interest in visiting.